2006
DOI: 10.1182/blood-2006-07-035279
|View full text |Cite
|
Sign up to set email alerts
|

Altered activation of AKT is required for the suppressive function of human CD4+CD25+ T regulatory cells

Abstract: Suppression by T regulatory cells (Treg IntroductionActive suppression of immune responses by T regulatory cells (Treg cells) is a key mechanism for induction and maintenance of peripheral tolerance. [1][2][3][4] The importance of Treg cells in vivo has been demonstrated in several mouse models: their absence results in systemic autoimmune disease, while their presence can inhibit antitumor, antiallergen, antiviral, and antiparasite immunity. [2][3][4][5] Knowledge of exactly how Treg cells arise, the precise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
186
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(200 citation statements)
references
References 56 publications
12
186
0
2
Order By: Relevance
“…Several studies investigated the role of Akt/mTOR signaling in Treg cells. Thereby, enforced activation of Akt or loss of PTEN, an upstream inhibitor of Akt-signaling, resulted in reversal of the suppressive function of Treg cells (41,42). Our results showed that hyperactivation of Akt/mTOR by IL-7 leads to repression of the DN T cell mediated suppression.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Several studies investigated the role of Akt/mTOR signaling in Treg cells. Thereby, enforced activation of Akt or loss of PTEN, an upstream inhibitor of Akt-signaling, resulted in reversal of the suppressive function of Treg cells (41,42). Our results showed that hyperactivation of Akt/mTOR by IL-7 leads to repression of the DN T cell mediated suppression.…”
Section: Discussionmentioning
confidence: 55%
“…However, Tregs were demonstrated to show diminished Akt pathway activation and an anergic cell fate (41,48). In addition, Tregs and type 1 Tregs initially were characterized as T cells with a special anergic phenotype that is necessary for their suppressive activity (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K-AKT-mTOR pathway is a crucial bifurcation point for inflammatory versus regulatory T cell programmes, as the activation of this pathway is required for the polarization and function of most T helper cells but is largely repressed in FOXP3 + T Reg cells 74,75 . AKT function is blunted in T Reg cells by the activity of PTEN, as well as by PH domain leucine-rich repeat-containing protein phosphatases (PHLPPs) that directly inactivate AKT, effectively rewiring their response to IL-2 to selectively activate STAT5, but not AKT [76][77][78] . Removal of this regulation in T Reg cells with PTEN deficiency results in severely compromised T Reg cell stability and in their conversion into inflammatory T H 1 and T H 17 cells 79,80 .…”
Section: Box 2 | Phenotypic Plasticity In Inflammatory and Regulatorymentioning
confidence: 99%
“…PKB isoform, which presumably would increase phosphorylated Foxo species, partially reversed the suppressive capacity of regulatory T cells in vitro, associated with restoration of their ability to produce several cytokines such as IFN-g, but not IL-2, without affecting expression levels of Foxp3, CTLA4, CD25, or granzymes A/B (Crellin et al, 2007). Foxo proteins therefore play diverse roles in multiple T cell subsets (Table 1).…”
Section: Foxo Proteins In T Cellsmentioning
confidence: 99%